PENGARUH MEDIA POWERPOINT TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR - Muhammad Nurwahidin; Amrina Izzatika; Dayu Rika Perdana; Anissa Fadya Haya; Aesti Meilandari (Program Studi PGSD Universitas Flores, 2024)
The problem in this study is the low learning outcomes of fourth-grade students in SD Negeri 3 Bumi Waras due to the fact that the educators have not provided creative and innovative learning media in the learning process, resulting in students' lack of active engagement in learning. This study aims to determine the influence of using PowerPoint media on the learning outcomes of thematic subjects among students. The research method used is quasi-experimental with a nonequivalent control group design. The population of this study consists of 76 students in the fourth grade. The research sample consists of 50 students selected using purposive sampling technique. The data collection techniques employed are observation, document analysis, and tests. The data analysis involves simple linear regression. The results of this research indicates that there is an influence of PowerPoint media on the learning outcomes of students in the fourth grade thematic subjects at SD Negeri 3 Bumi Waras in the academic year 2022/2023.